Organizational innovation in the multinational enterprise: Internalization theory and business history - da Silva Lopes, Teresa; Casson, Mark; Jones, Geoffrey (Journal of International Business Studies, 2019)
This article engages in a methodological experiment by using historical evidence to challenge a common misperception about internalization theory. The theory has often been criticized for maintaining that it assumes a hierarchically organized MNE based on knowledge flowing from the home country. This is not an accurate description of how global firms operate in recent decades, but this article shows it has never been true historically. Using longitudinal data on individual firms from the nineteenth century onwards, it reveals evidence of how entrepreneurs and firms with multinational activity faced with market imperfections changed the design of their headquarters and their organizational structures.